Evaluating the Effects of Lost and Found Policies on the Efficiency of Hotel Housekeeping Operations and the Trust of Guests - Wijoyo, Adhistyo; Kurniawan, Surya; Intiar, Septa; Umar A.J.; Bayu A.P (International Journal of Economics, Business Management and Accounting (IJEBMA), 2024)
This study examines the influence of lost and found protocols on the effectiveness of housekeeping operations and the level of trust from guests, with a specific emphasis on the integration of RFID technology in New York Hotel Melaka The research used a qualitative methodology, including semi-structured interviews, case study observations, and document reviews. It discovered that the implementation of RFID technology resulted in a 50% decrease in the time needed to handle and return lost goods. This improvement greatly enhanced operational efficiency and visitor satisfaction. The technology also enhanced staff work satisfaction by reducing manual administrative duties. The limitations of the research are twofold: firstly, it only focuses on a particular hotel, and secondly, it excludes alternative technology options. These factors may impact the generalizability of the findings. Hotels should combine innovative technology with thorough staff training and standardized procedures to improve lost and found management. This research provides novel insights on the advantages of RFID technology in managing lost and found items, so adding to a more comprehensive knowledge of how technology may improve hotel operations and increase visitor experiences